Perencanaan Strategis SI/TI dengan menggunakan Metode Ward And Peppard pada Dinas Perumahan Rakyat dan Kawasan Permukiman Daerah Kota Tomohon - Ferren Feibiola Pusung; Penidas Fiodinggo Tanaem (STMIK Budi Darma, 2023)
The Department of Public Housing and Regional Settlements of Tomohon City is an agency in Tomohon City, the agency is still lacking in the use of information system applications and information technology so that it affects a lot in the development of business in the office, therefore strategic planning is needed in order to support and be able to develop the business in the office. Information system planning is a systematic approach to what is considered the most efficient in meeting the needs of information. The method used in this study is Ward and Peppard, in the Ward and Peppard method there are analyses, namely PEST, Value Chain, SWOT and McFarlan Strategic Grid. The results of this research are in order to help and facilitate to overcome the problems that exist in the service